Usability analysis of a Virtual Reality device in a social awareness experience - Pinheiro, Paula (2024)
This article presents the results of a usability evaluation of the Google Cardboard Virtual Reality (VR) device in an immersive experience through a 360° video of a social nature, entitled Amazônia Adentro. The research was motivated by the question about the possibility of bringing together different social contexts based on impacts caused by a virtual experience, and in this case, using a low-cost device, with a view to iden- tifying possible weaknesses and/or potential uses in the context. trained, as well as enabling practice in a scaled manner. To this end, research of an inferential nature was developed, based on usability tests of the device with a sample of users, based on the three pillars provided for by ISO 9241 (11), namely: efficiency, effectiveness and satis- faction. In this sense, in general terms, the study carried out indicated that the device in question, for the application evaluated and in the chosen context of use, proved to be an interesting and viable resource for using VR technology.